2018
DOI: 10.1038/s41388-018-0426-6
|View full text |Cite
|
Sign up to set email alerts
|

ATP in the tumour microenvironment drives expression of nfP2X7, a key mediator of cancer cell survival

Abstract: The ATP-gated receptor P2X is expressed in multiple malignant tumours including neuroblastoma, melanoma, prostate, lung and breast. P2X has a significant role in mediating diverse cell responses, which upon dysregulation are associated with tumour initiation and development. The rapid, ATP-mediated activation of P2X induces a fast-inward cation current in cells. However, prolonged ATP-mediated activation of P2X leads to formation of a pore that increases membrane permeability and eventually causes cell death. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
192
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(207 citation statements)
references
References 47 publications
14
192
0
1
Order By: Relevance
“…Another form of P2X7R, which is not able to form a functional pore and termed as non-pore functional P2X7R (nfP2X7R), has been described recently [101]. Researchers found that antibodies against amino acid sequence specifically for nfP2X7R also had a key role in cancer growth [108], which documented that antagonists specifically for nfP2X7R may be potential effective therapeutic agents in cancer therapy.…”
Section: P2 Receptors As Tumor Therapeutic Targetsmentioning
confidence: 99%
“…Another form of P2X7R, which is not able to form a functional pore and termed as non-pore functional P2X7R (nfP2X7R), has been described recently [101]. Researchers found that antibodies against amino acid sequence specifically for nfP2X7R also had a key role in cancer growth [108], which documented that antagonists specifically for nfP2X7R may be potential effective therapeutic agents in cancer therapy.…”
Section: P2 Receptors As Tumor Therapeutic Targetsmentioning
confidence: 99%
“…The P2X7 receptor is found in several types of tumors, such as neuroblastoma, melanoma, prostate, lung, and breast cancer. P2X7 expression is commonly associated with cancer cell survival, proliferation, and metastatic potential; upon dysregulation, the P2X7 receptor is associated with tumor initiation and development ( Gilbert et al, 2019 ).…”
Section: Cancermentioning
confidence: 99%
“…In healthy tissues, P2X7 is expressed mainly in the central nervous system (CNS), peripheral nervous system (PNS), and in immune cells, which supports its emergence as a target for chronic pain and chronic inflammatory diseases . P2X7 is also overexpressed in a number of cancer types, potentially driving tumor development and survival (Adinolfi et al, 2002;Adinolfi et al, 2009;Adinolfi et al, 2012;Barden et al, 2014;Amoroso et al, 2015;Barden et al, 2016;Gilbert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%